Exploration of Phytochemicals as Anti-biofilm Agents against Pathogenic Bacteria: Their Potential and Challenges - Banerjee, Debolina; Biswas, Poulomi; Mazumder, Kamalika; Palai, Sangita; Hossain, Chowdhury Mobaswar; Karmakar, Sanmoy; Biswas, Kaushik (Infectious Disorders - Drug Targets, 2025)
Multicellular surface-attached populations of bacteria embedded in the extracellular matrix are known as biofilms. Bacteria generally preferred to grow as biofilms. Quorum sensing (QS), detection of density of cell population through gene regulation, has been found to play an important role in the production of biofilms. Biofilm formation can increase the severity of infections that can lead to morbidity or mortality. Bacteria living within biofilms have a higher pattern of adaptive resistance to antibiotics. Antibiotic resistance is a barrier in the treatment of biofilms-induced acute to chronic infections such as post-surgery infections, surgery-associated wound infections, endocarditis, joint infections, burn-related wound infections occurred, ventilator-associated pneumonia, etc. So it is urgent to discover or find out potent new drugs in fight against infectious diseases such as biofilms-associated infections. Medicinal plants or herbs are a rich source for fighting with biofilms-mediated infections. Phytochemicals have exhibited significant effects in the prevention of biofilms formation against different bacteria that are causing infections. Purified compounds such as berberine, tetrandrine, embelin, xanthorrhizol, bakuchiol, etc., exhibited promising biofilm inhibition actions against different pathogenic bacteria. Plant extracts that contain several phytochemicals are evaluated for its biofilm’s inhibition property, and have shown significant potential in biofilm formation. Antibiofilm agents act by distinct mechanisms such as inhibiting the adherence of biofilms in a surface, preventing the biofilm formations, disrupting the matured biofilms, etc. This study is intended to reiterate about possibilities of plant extracts and purified compounds in the treatment of the prevention of bacterial biofilms-related infections.
Keywords: plant derived anti-microbial